The Bioinsecticide of The Essential Oil of Citronella (Cymbopogon citratus) Against Black Ants (Crematogaster sp) - Wibowo, Muhamad Agus; Wahyuni, Sri; Ardiningsih, Puji; Jayuska, Afghani (Jurnal ILMU DASAR, 2025)
The essential oil of Cymbopogon citratus has the potential as a natural bioinsecticide in safe pest control. This research aimed to determine the chemical content and activity of the essential oil of C. citratus from Punggur village, Kubu Raya district, in killing black ants. This research was conducted in two stages: (i) Distillation of citronella oil and its characterization by IR and GC-MS, and (ii) bioinsecticide test of the oil on black ants (Crematogaster sp). The distillation results gave a yield of 0.43%, which contained 47 compounds with 7 main compounds namely beta.-Myrcene (9.98%), iso-geranial (7.25%), linalool (2.04%), geranyl acetate (2 .39%), geranic acid(1.07%), citral (Z)-(14.97%), and citral (E)-(4.71%). Characterization with IR showed that there were absorption wavelengths of 3500 cm-1 (C-OH), 3086 cm-1 (C-H alkenes), 2920 cm-1 (C H alkanes), 2856 cm-1 and 2748 cm-1 (C-H aldehyde), 1716 cm-1 and 1674 cm-1 (C=O). The anti-ant activity test using various concentrations gave an LCM100 value of 1% and an LC50 of 0.016%. From the results of the study, it can be concluded that the essential oil of citronella leaves is a bioinsecticide against Crematogaster sp.